영작문 활동 중 동료 피드백에 대한 예비교사들의 인식 - 김희정(Heejung Kim); 이제영(Je-Young Lee); 장소영(So Young Jang) (한국콘텐츠학회 논문지, 19(1), 2019)
The purpose of this study is to investigate the perception of pre-service secondary English teachers on peer feedback in English composition. For this purpose, a total of 37 students who took the English composition class for 15 weeks participated in the survey. After completing the survey, data were analyzed to find out the students' perception on peer feedback performed in their English composition class through frequency analysis and descriptive statistics. The findings of this study are as follows: First, the students showed positive attitudes towards on peer feedback activities. Second, the participants had received considerable help in the content, ideas and organization of their composition. Third, noticing that they all have made similar mistakes in their writing, the subjects were relieved to know that they are not falling behind their other colleagues. Fourth, the subjects did not trust the feedback contents among the peers, which were found in both the feedback giver and receiver. In particular, feedback from peers who had low English proficiency was rarely helpful. Fifth, the students were afraid that their relationship might become uncomfortable with peers when they pointed out peer's writing errors or made specific suggestions about their peer's writing. Finally, pedagogical implications were discussed based on the research findings. 본 연구의 목적은 영어 작문 수업 중 이루어진 동료 피드백 활동에 대한 예비 영어교사들의 인식을 살펴보는 것이다. 이를 위해 15주간 영어 작문 수업을 수강하는 총 37명의 학생들이 설문에 참여하였고, 설문의 얻어진 데이터를 통해 동료 피드백 활동에 대한 학생들의 인식을 빈도분석, 기술통계를 통해 분석하였다. 연구 결과는 다음과 같다. 첫째, 동료 피드백 활동에 참여한 학생들은 긍정적 태도를 보였다. 둘째, 참여자들은 작문 결과물의 내용, 아이디어 조직 부분에서 특히 큰 도움을 받았다. 셋째, 학생들은 자신을 비롯한 모든 학생들이 유사한 오류를 범한다는 것을 알게 되면서 다른 학생들에 비해 작문 실력이 크게 뒤처지지 않는다는 점에 안도감을 느꼈다. 넷째, 피드백을 주는 입장과 받는 입장 모두에서 동료 피드백의 내용을 크게 신뢰하지 않았다. 특히 영어 능력이 낮은 동료로부터 받은 피드백은 큰 도움이 되지 않았다. 다섯째, 학생들은 동료의 오류를 지적하거나 너무 자세한 제안을 했을 때 그들의 관계가 불편해질 것에 대해 걱정하였다. 마지막으로 연구 결과를 바탕으로 교육적 시사점을 제언하였다.